2007
DOI: 10.1152/ajpgi.00024.2006
|View full text |Cite
|
Sign up to set email alerts
|

Increased intestinal permeability in obese mice: new evidence in the pathogenesis of nonalcoholic steatohepatitis

Abstract: October 5, 2006; doi:10.1152/ajpgi.00024.2006.-A small percentage of pathologically obese subjects with fatty livers develop histological signs of necroinflammation and fibrosis, suggesting a variety of cofactors in the pathogenesis of obesity-related liver diseases including nonalcoholic steatohepatitis. Since several observations have linked bacterial endotoxins to liver damage, the aim of this study was to determine the effect of obesity on intestinal mucosal integrity and portal blood endotoxemia in two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
630
4
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 735 publications
(679 citation statements)
references
References 58 publications
33
630
4
12
Order By: Relevance
“…In addition, genetically obese fa/fa rats and ob/ob mice quickly develop steatohepatitis after exposure to low doses of LPS (41). This is in agreement with a two-to four-times-increased endotoxemia characterizing db/db and ob/ob mice due to an increased intestinal permeability (42). Furthermore, polymyxin B treatment, which specifically eliminates Gram-negative bacterias and further quenches LPS, diminishes hepatic steatosis (43).…”
Section: Discussionsupporting
confidence: 69%
“…In addition, genetically obese fa/fa rats and ob/ob mice quickly develop steatohepatitis after exposure to low doses of LPS (41). This is in agreement with a two-to four-times-increased endotoxemia characterizing db/db and ob/ob mice due to an increased intestinal permeability (42). Furthermore, polymyxin B treatment, which specifically eliminates Gram-negative bacterias and further quenches LPS, diminishes hepatic steatosis (43).…”
Section: Discussionsupporting
confidence: 69%
“…have recently demonstrated that obese and diabetic mice (ob/ob and db/db) exhibited significantly higher plasma endotoxin levels, which correlated to higher plasma inflammatory markers [30]. Multiple Pearson's correlations analysis of our data revealed that endotoxaemia positively correlated with glucose intolerance, fasted insulinaemia, inflammatory markers, adipose tissue and body weight gain, while bifidobacteria negatively correlated with these parameters.…”
Section: Discussionsupporting
confidence: 52%
“…Glucose tolerance test Oral glucose tolerance tests were performed after 13 weeks of treatment in mice that had been fasted for 6 h. Glucose was orally administered (3 g/kg body weight, 660 g/l glucose solution) and blood glucose determined through a glucose meter (Roche Diagnostics, Meylan, France) using 3.5 μl of blood collected from the tip of the tail vein before and at administration of glucose load (−30 and 0 min) and after glucose load (15,30,60, 90, 120 min). To assess plasma insulin concentration, 20 μl of blood was sampled 30 min before and 15 min following the glucose load.…”
Section: Methodsmentioning
confidence: 99%
“…21,22 However, the exact mechanisms involved in sugar and particularly fructose-induced NAFLD are still poorly understood. Here, by feeding mice lacking the endotoxin receptor TLR-4 chronically with a moderate fructose-enhanced diet (e.g., 30% fructose in drinking solutions) we further tested the hypothesis that the endotoxin-induced activation of hepatic Kupffer cells resulting from intestinal bacterial overgrowth and increased intestinal permeability 13,14 is a key factor in the onset of fructose-induced NAFLD. Indeed, despite similarly elevated plasma endotoxin levels in portal plasma, hepatic steatosis in livers of TLR-4 mutant mice fed with fructose solution, and plasma ALT levels were markedly lower than in wildtype controls exposed to fructose.…”
Section: Discussionmentioning
confidence: 99%
“…10 In support of these findings, Baraona et al 12 reported that the bacterial flora of rodents can ferment carbohydrates to alcohol when intestinal stasis allows their overgrowth in the upper parts of the gastrointestinal tract. Furthermore, an increased mucosal permeability in the small intestine, which was found in genetically obese mice 13 and after high-fat feeding in mice, 14 leads to portal endotoxemia. Gut-derived bacterial endotoxin is brought to the liver in the portal circulation, thereby activating Kupffer cells, the resident hepatic macrophages by way of the Toll-like receptor 4 (TLR-4) complex on the cell surface.…”
mentioning
confidence: 98%